The Geographical Factors on the Failure of Bricklin Canada Limited - Williamson, Shawn (My University, 1991)
This research paper investigates the factors on business failure in the Maritime region of Canada via a sample study of Bricklin Canada Ltd. This sample illustrates· the effects of regionalism and geographic location on the manufacturing industry. This company's failure will be examined as how it arose from reasons including geographic isolation, regional disparities, externalities, scale economies and external forces. A study of this particular industrial failure will lend insights regarding the needs of future regional policy. Although businesses from these marginalized regions of Canada have realized success, there are still a great many steps yet to take. A means must be found to reintroduce a self-sustaining economy to these regionalized areas of Canada where it is lacking.
Keywords: geographic factors; Bricklin; Bricklin Canada; business failure